UK magnetosphere, ionosphere and solar-terrestrial (MIST) awards taskforce: A perspective - Walach, Maria-Theresia; Agiwal, Omakshi; Allanson, Oliver; Owens, Mathew J.; Rae, I. Jonathan; Sandhu, Jasmine K.; Smith, Andy (Frontiers in Astronomy and Space Sciences, 2022)
“We don’t live in a meritocracy, and to pretend that simple hard work will elevate all to success is an exercise in willful ignorance.” (Reni Eddo-Lodge wrote in her book “Why I’m no longer talking to white people about race” (Published by Bloomsbury, London, p. 79, ISBN: PB: 978-1-4088-7)). This echoes through the academic scientific community, and can be readily seen in the demographics of physics prize winners. Prizes are extremely influential in both projecting how a community is outwardly perceived and actively shaping the community through facilitating career advancement. But how can biases in the awards process be addressed? We do not pretend to have all the answers, nor is there a single solution, but in this perspective article we explore one pragmatic approach to tackling chronic underrepresentation in the space sciences when it comes to nominations for awards and prizes.